An In-depth Analysis of Speech Styles in English language - Nurul Hidayah; Lusiana Suciati Dewi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study examines the role of speech style in learning English among students. This research is research using a qualitative approach. The population in this study is an X-class student of AT-tawazun Kalijati Subang's MA. Interviews and random sampling techniques are used for sample-taking. The results of the study show that the influence of the student's speaking style in learning English affects the level of English skills of students. Some aspects that affect the student's speech style are the daily activities of the student, such as speaking English in theys spare time. Classes that encourage learning are also effective.